Draped in Meaning: The Evolving Symbolism of the Black Abaya in Saudi Arabia - Al Saud, Latifa S. (Gulf Education and Social Policy Review (GESPR), 2025)
This study explores the symbolism of the Black Abaya within contemporary Saudi society. This loose-fitting, full-length garment, prevalent as an item of women’s clothing in the Arabian Peninsula, has a long history as the standard modest dress for day-today wear among Muslim women. In recent years, academic and media attention toward the attire in the West has seen it come to serve as a symbol for Muslim womanhood sometimes associated with religious extremism, oppression, and personal agency. This interpretation has underscored the need for greater understanding and appreciation of the diverse cultural practices and traditions associated with the Abaya within Arab and Muslim societies. This study investigates how contemporary Saudi women interact with and explore the garment, especially their relationship with the traditional Black Abaya. This is pursued through undertaking ethnographic research consisting of interviews, observations, autoethnographic methods, and documentary analysis. The study notes the ambiguous and diverse interpretations of the Abaya as well as a trend toward embellishing the traditional Black Abaya form to better suit the needs of modern Saudi women for self-expression.